A Conflict on Baha‘ism and Islam in 1922: Abdullah Cevdet and State Religious Agencies - Ayşe Polat (İnsan & Toplum)
This paper investigates Abdullah Cevdet’s 1922 article on Baha’ism as well the reaction of the state authorities, particularly that of two Meşihat councils. After briefly discussing the author’s biography and journalistic activities, primarily his periodical İctihad, the paper focuses on the essay’s content by investigating the historical context, namely, the post-World War I years, during which he articulated his ideas on Baha’ism as a religion of peace and nonviolence. Close attention is also paid to the distinctions Cevdet drew among Baha’ism, Islam, and Christianity regarding their essential origins and how they developed in human time, i.e. history. The rest of the article details the presence of Ottoman religious censorship mechanisms on periodical publications during the Armistice years. In this regard, the state’s decision to authorize the Tetkik-i Mesahif ve Müellefat-ı Şeriyye Meclisi and the Daru’l-Hikmeti’l İslamiye to approve or reject Islamic publications are stud- ied closely, especially with respect to their criticism of Cevdet’s essay. The criteria and rationale they deployed in condemning it are analyzed through their own archival records.